Interaction of MOPS buffer with glass–ceramic scaffold: Effect of (PO4)3− ions in SBF on kinetics and morphology of formatted hydroxyapatite. Issue 5 (16th December 2019) - Horkavcová, Diana; Rohanová, Dana; Stříbny, Adam; Schuhladen, Katharina; Boccaccini, Aldo Roberto; Bezdička, Petr
Abstract: The international standard ISO 23317:2014 for the in vitro testing of inorganic biomaterials in simulated body fluid (SBF) uses TRIS buffer to maintain neutral pH. In our previous papers, we investigated the interaction of a glass–ceramic scaffold with TRIS and HEPES buffers. Both of them speeded up glass–ceramic dissolution and hydroxyapatite (HAp) precipitation, thereby demonstrating their unsuitability for the in vitro testing of highly reactive biomaterials. In this article, we tested MOPS buffer (3‐[N‐morpholino] propanesulfonic acid), another amino acid from the group of "Goods buffers". A highly reactive glass–ceramic scaffold (derived from Bioglass®) was exposed to SBF under static–dynamic conditions for 13/15 days. The kinetics and morphology of the newly precipitated HAp were studied using two different concentrations of (PO4 ) 3− ions in SBF. The pH value and the Si IV, Ca 2+, and (PO4 ) 3− concentrations in the SBF leachate samples were measured every day (AAS, spectrophotometry). The glass–ceramic scaffold was monitored by SEM/EDS, XRD, WD‐XRF, and BET before and after 1, 3, 7, 11, and 13/15 days of exposure. As in the case of TRIS and HEPES, the preferential dissolution of the glass–ceramic crystalline phase (Combeite) was observed, but less intensively. The lower concentration of (PO4 ) 3− ions slowed down the kinetics of HAp precipitation, thereby causing the disintegration of the scaffold structure. This phenomenon shows that the HAp phase was predominately generated by the presence of (PO4 ) 3− ions in the SBF, not in the glass–ceramic material. Irrespective of this, MOPS buffer is not suitable for the maintenance of pH in SBF.